The talking T. Rex - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2003)
Dink, Josh, and Ruth Rose investigate the theft of a great deal of money from the belly of a nearly life-size Tyrannosaurus Rex model that their friend, Jud Wheat, is using to raise money for a dinosaur museum.
"A Stepping Stone book."
"T"--Spine.
4.8
3-6
Keywords: Robbers and outlaws -- Fiction; Fourth of July -- Fiction; Stealing -- Fiction; Mystery and detective stories; Dinosaurs -- Fiction; Thieves -- Fiction; Fourth of July -- Fiction; Theft -- Fiction; Mystery fiction; Dinosaurs -- Fiction